2008
DOI: 10.1007/s11596-008-0623-6
|View full text |Cite
|
Sign up to set email alerts
|

Plastic changes of synapses and excitatory neurotransmitter receptors in facial nucleus following facial-facial anastomosis

Abstract: The remodeling process of synapses and neurotransmitter receptors of facial nucleus were observed. Models were set up by facial-facial anastomosis in rat. At post-surgery day (PSD) 0, 7, 21 and 60, synaptophysin (p38), NMDA receptor subunit 2A and AMPA receptor subunit 2 (GluR2) were observed by immunohistochemical method and semi-quantitative RT-PCR, respectively. Meanwhile, the synaptic structure of the facial motorneurons was observed under a transmission electron microscope (TEM). The intensity of p38 immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…An explanation for the poor functional recovery of the facial nerve is the abnormal activity pattern of the axotomized motor neurons, which necessarily involves the constitution and activity of ionotropic glutamate receptors . Our study indicated that the expression levels of GluR2, GluR3, and NR1 mRNA were higher, and that the expression of GluR1, GluR4, NR2a, NR2b, NR2c, and NR2d mRNA were lower in dormant FMNs than in reinnervating FMNs.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…An explanation for the poor functional recovery of the facial nerve is the abnormal activity pattern of the axotomized motor neurons, which necessarily involves the constitution and activity of ionotropic glutamate receptors . Our study indicated that the expression levels of GluR2, GluR3, and NR1 mRNA were higher, and that the expression of GluR1, GluR4, NR2a, NR2b, NR2c, and NR2d mRNA were lower in dormant FMNs than in reinnervating FMNs.…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, detecting and sampling processes, including the manual collection of specimens, in situ hybridization, or regular RT-PCR, would unavoidably affect the reproducibility of results and thereby decreased the power of a study. 4,5 Our previous study showed that the GluR2 mRNA level in the whole facial nucleus region at the operated side did not exhibit evident changes as compared with the normal side. 4 Yet, this study, by employing LCM, found that GluR2 mRNA level varied with different FMNs in the facial nucleus at the operated side.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations